IMPLEMENTATION OF INTEGRATED MARKETING COMMUNICATION IN MARKETING THE COMPANY (CASE STUDY ARIMBA AT BISMA) - Cahyani, Ni Putu Mia; Artani, Ketut Tri Budi; Alam, Helmy Syakh (Institut Bakti Nusantara, 2024)
This research examines the application of Integrated Marketing Communication (IMC) in marketing Arimba at Bisma company in the accommodation sector. Through a qualitative descriptive approach, the research analyzed the effectiveness of IMC strategies before and after they were implemented, using observation and interview techniques. The results show that Arimba at Bisma has carefully implemented the five elements of IMC, especially in the utilization of social media such as Facebook and Instagram to expand its reach. Direct marketing strategies and collaboration with local parties have also successfully expanded market share. From this study, it is concluded that the application of well-integrated IMC has successfully increased brand awareness, customer interaction, and direct sales. This approach is the key to success in effective marketing strategies at Arimba at Bisma, and provides important insights in the context of the accommodation industry.